Liquidity black holes: And why modern financial regulation in developed countries is making short-term capital flows to developing countries even more volatile - Avinash Persaud (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Modern financial regulation has been about the spread of market-sensitive riskmanagement systems for banks, the spill-over of this approach to other financial institutions and the retreat of regulatory ambition. There is evidence that these trends are leading to a more fragile financial system, more prone to concentration and `liquidity black holes'. The most glaring effects of these trends are felt in the pro-cyclicality and volatility of capital flows to risky markets. The root of the problem is that the liquidity of financial markets requires diversity, but all these trends are serving to reduce the diversity of behaviour of market participants.
Keywords: G14; G15; G18; 330; financial regulation; liquidity black holes; investor behaviour; Kapitalverkehrspolitik; Bankenpolitik; Gesamtwirtschaftliche Liquidität; Entwicklungsländer